PENGARUH LATIHAN PILATES TEHADAP PENINGKATAN FLEKSIBILITAS LUMBO-PELVIC LANSIA PADA ANGGOTA PERSATUAN DIABETES INDONESIA (PERSADIA) JAKARTA TIMUR - Hariandja, Andy Martahan Andreas; Sariana, Erna; Hidayati, Wukir Asih Din (Jurnal Fisioterapi dan Kesehatan Indonesia, 2025)
Background: Flexibility is the ability of joints, muscles, ligaments, which surround them to move freely within the maximum range of motion. The cause of decreased flexibility with increasing age, the range of motion of joints decreases thereby affecting structural changes that can reduce tissue elasticity. One way to improve lumbo pelvic flexibility is with pilates exercises. Research Objectives: To determine the effect of pilates exercise on increasing lumbo pelvic flexibility in the elderly in members of the Indonesian Diabetes Association (PERSADIA) in East Jakarta. Methods: This type of research is pre-experimental with a one group pretest – posttest approach. The number of samples is 17 people. The intervention given was Pilates exercise. Results: The average lumbopelvic flexibility of the elderly before the intervention was 7.5 and after the intervention was 16.7. The results of statistical tests using the Paierd Sample T-test obtained a p-value of 0.000. Conclusion: From the results of this study it can be concluded that there is an effect of pilates training on lumbo pelvic flexibility in the elderly.